Expression of ROS-responsive genes and transcription factors after metabolic formation of H2O2 in chloroplasts - Balazadeh, Salma; Jaspert, Nils; Arif, Muhammad; Mueller-Roeber, Bernd; Maurino, Veronica G. (Frontiers in Plant Science, 2012)
Glycolate oxidase (GO) catalyses the oxidation of glycolate to glyoxylate, thereby consuming O2 and producing H2O2. In this work, Arabidopsis thaliana plants expressing GO in the chloroplasts (GO plants) were used to assess the expressional behaviour of reactive oxygen species (ROS)-responsive genes and transcription factors (TFs) after metabolic induction of H2O2 formation in chloroplasts. In this organelle, GO uses the glycolate derived from the oxygenase activity of RubisCO. Here, to identify genes responding to an abrupt production of H2O2 in chloroplasts we used quantitative real-time PCR (qRT-PCR) to test the expression of 187 ROS-responsive genes and 1,880 TFs after transferring GO and wild-type plants grown at high CO2 levels to ambient CO2 concentration. Our data revealed coordinated expression changes of genes of specific functional networks 0.5 h after metabolic induction of H2O2 production in GO plants, including the induction of indole glucosinolate and camalexin biosynthesis genes. Comparative analysis using available microarray data suggests that signals for the induction of these genes through H2O2 may originate in the chloroplast. The TF profiling indicated an upregulation in GO plants of a group of genes involved in the regulation of proanthocyanidin and anthocyanin biosynthesis. Moreover, the upregulation of expression of TF and TF-interacting proteins affecting development (e.g., cell division, stem branching, flowering time, flower development) would impact growth and reproductive capacity, resulting in altered development under conditions that promote the formation of H2O2.